Enhancing the Quantum Anomalous Hall Effect by Magnetic Codoping in a Topological Insulator. Issue 1 (10th November 2017) - Ou, Yunbo; Liu, Chang; Jiang, Gaoyuan; Feng, Yang; Zhao, Dongyang; Wu, Weixiong; Wang, Xiao‐Xiao; Li, Wei; Song, Canli; Wang, Li‐Li; Wang, Wenbo; Wu, Weida; et al.
Abstract: The quantum anomalous Hall (QAH) effect, which has been realized in magnetic topological insulators (TIs), is the key to applications of dissipationless quantum Hall edge states in electronic devices. However, investigations and utilizations of the QAH effect are limited by the ultralow temperatures needed to reach full quantization—usually below 100 mK in either Cr‐ or V‐doped (Bi, Sb)2 Te3 of the two experimentally confirmed QAH materials. Here it is shown that by codoping Cr and V magnetic elements in (Bi, Sb)2 Te3 TI, the temperature of the QAH effect can be significantly increased such that full quantization is achieved at 300 mK, and zero‐field Hall resistance of 0.97 h / e 2 is observed at 1.5 K. A systematic transport study of the codoped (Bi, Sb)2 Te3 films with varied Cr/V ratios reveals that magnetic codoping improves the homogeneity of ferromagnetism and modulates the surface band structure. This work demonstrates magnetic codoping to be an effective strategy for achieving high‐temperature QAH effect in TIs. Abstract : In Cr and V codoped (Bi, Sb)2 Te3 topological insulator films, the quantum anomalous Hall (QAH) effect is achieved at 300 mK, about one order of magnitude higher than that for singly Cr‐ or V‐doped ones, and the energy scale of QAH state reaches 1.4 K. The transport study of the codoped films with varied Cr/V ratios reveals the origins of enhancement.